The catacombs of Anubis at North Saqqara an archaeological perspective - Nicholson, Paul T. 1960-; Ikram, Salima 1965-; Mills, Steve 1969-; Bertini, Louise 19XX- (Peeters, 2021)
In 1897 Jacques de Morgan published a map of the Memphite necropolis, showing for the first time a pair of catacombs for mummified dogs. No further information was given and the catacombs remained largely un-investigated until the 21st century. In 2009 the Catacombs of Anubis Project was set up by Cardiff University who worked in collaboration with the Egyptian Supreme Council for Antiquities in an attempt to understand the larger of the two catacombs.0This publication describes the work of the Catacombs of Anubis Project. It examines the way in which the catacomb was created and the likely phases of its development in the Late and Ptolemaic periods. The way in which the many thousands of animal mummies were procured is discussed in the light of modern faunal analysis and these results are combined with a new survey of the site to give a picture of the functioning of the cult at Saqqara. Finally, the way in which the monument may have been re-used in the post-pharaonic era is discussed.0The results will be of interest to all those interested in animal mummies and in the development of catacombs as well as those concerned with the evolution of the sacred landscape of Saqqara.
Keywords: Ausgrabung; Funde; Hunde-Nekropole -- Sakkara; Mummified animals / Egypt; Dogs / Egypt / Religious aspects; Catacombs / Egypt / Ṣaqqārah; Animals / Cult; Gods, Egyptian; Catacombs; Dogs / Religious aspects; Mummified animals; Egypt; Egypt / Ṣaqqārah